Unidirectional pedestrian flow in a corridor involving individuals with disabilities: a modified floor field modelling approach. (28th July 2021) - Fu, Libi; Liu, Yuxing; Shi, Yongqian; Zhao, Yongxiang
Abstract: In this paper, a modified floor field model is presented to study crowd dynamics involving individuals with disabilities (i.e. pedestrians on crutches, seniors with sticks, pedestrians in manual wheelchairs and blind pedestrians). Multi-speed characteristics, overtaking and helping behaviors are considered in our model. Through simulations in unidirectional pedestrian flow in a corridor, it is observed that overtaking behavior has a positive effect on pedestrian flow at low density. Helping behavior can significantly improve the maximum flow rate and critical density of a system. In comparison with overtaking behavior, helping behavior is more beneficial to heterogeneous crowd movement, when density is higher than the critical density. The phenomenon that the proportion of individuals with disabilities has a negative influence on crowd movement efficiency is reproduced. It is hoped that this study will enrich movement rules and modeling approaches for individuals with disabilities, and be helpful in crowd management and evacuation organization.